Efeito do tratamento termomecânico na microestrutura e propriedades mecânicas da ligA CuAl17Mn9 contendo 2.0 at% de cromo - Araújo Junior, Francisco Wlaudy Erimar Lourenco de (2022)
CuAlMn alloys are quite attractive to various applications due to their unique properties of form memory effect (SME) and overelasticity (SE). Thus, there is a continuous interest in SMAs based on Cu due to its low cost, pronounced thermal conductivity, good processability, as well as the highly cushioned properties, also combined with their elastocalorimetry properties. However, these alloys have their limitations associated with their high fragility which is attributed to high elastic anisotropy, ordered phase formation and rude grain formation. In this work, we seek to improve the properties by applying the process of hot and cold rolling in a CuAl17Mn9Cr2 alloy. This alloy was elaborated in an induction oven in the form of rectangular ingots. The formation of a microstructure was observed the Beta and Alpha phases, as well as chromium -rich intermetallic compounds with a fewer Mn presence. This alloy can easily be rolled into room temperature. Cyclic traction testing tests showed the reach of a 5 % overlap.